(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Schizoaffective disorder is a chronic mental health problem characterized by symptoms of Schizophrenia such as hallucinations and delusions, as well as symptoms of a mood disorder such as mania or depression. Many people who suffer from schizoaffective disorder are frequently given incorrect diagnoses because it exhibits signs that are similar to those of multiple mental health disorders. Schizoaffective disorder occur about one-third as frequently as schizophrenia, and the lifetime prevalence appears to be around 0.3%. But men often develop the disorder at an earlier age than women. Both mood stabilizers and antipsychotics are used in contemporary management. In Ayurveda, this disorder can be included under Unmada, as it presents the clinical features of Unmada. Unmada includes the Vibhrama of 8 factors including Manas and Budhi. A 31 year old female patient hailing from Kannur district admitted at Government Ayurveda Research Institute for Mental Health and Hygiene, Kottakkal, 6 months back. She had increased fear that something bad will happen to her, the world and all people are against her, her parents are suffering due to her mistake; since 3 years. According to the informant, she had increased fear, decreased sleep, increased suspicion, suicidal thought, always tells that police is coming to arrest her, others are controlling her, since 3 years. The case was diagnosed as Kaphavataja Unmada considering the Dosha predominance and treatments included Sodhana, Samana and Yoga. There was significant improvement in the score of Positive And Negative Symptom Scale for the assessment of Schizophrenia and Hamilton’s Depression Rating Scale for the assessment of mood disorder, after the IP management and follow-up. The case study emphasizes the value of Ayurvedic treatment approaches in treating schizophrenia affective disorder.